Generalized discrimination thresholds and evaluation of simultaneous variations in the intensity and frequency of a tone - CZAJKOWSKI, Alicja (Archives of Acoustics, 1981)
The investigations presented in this paper were based on the concept of an interrelation between simultaneously evaluated variations in loudness and pitch of the same tonal signal with varying intensity and frequency. As an example, some elements of this interrelation – related to the perceptibility and to the evaluation of the magnitude of variations in loudness and pitch –were examined for a chosen tone. The results obtained were represented in the form of new, so-called generalized, discrimination thresholds and of the curve of the variations in loudness and pitch sensed to be equal. The results permit the statement that it is possible to sum up the subthreshold effects caused by the simultaneous variations in the signal intensity and frequency and thus to obtain the superthreshold effect in the form of a sensation of loudness variations. For greater variations in the physical parameters, a sort of mutual "masking" of the simultaneous variations in loudness and pitch of the same tone was found, and in the case when both variations were audible simultaneously it was found that it was possible to compare these in terms of magnitude.